Structural Transfer In Third Language Acquisition: The Case Of Lingala-French Speakers Acquiring English - Mwamba Kabasele, Philothé (My University, 2018)
This paper tests the claims of Cumulative Enhancement Model, the ‘l2 status factor’, and the Typological Primacy Model in investigating how l1 Lingala, l2 French speakers express in English an event which took place and was completed in the past. The linguistic phenomena understudy informs us that English uses the simple past in a past-completed event while French and Lingala use the ‘passé composé’ and the remote or recent past, respectively. The study circumscribes the tense similarities and differences between the three languages. The paper strives to answer the questions on which previously acquired language between the l1, l2, or both l1 & l2 overrides in l3 syntactic transfer. The paper aims to determine whether the l2 is the privileged source of syntactic transfer even when the l1 offers syntactic similarities with the l3. Finally, the study purports to determine whether subjects are more accurate when communicating in explicit mode than in implicit mode. That is, the study further aims to investigate whether subjects make less transfer errors in a task that promotes reliance on explicit knowledge than they do in task that promotes reliance on implicit knowledge. The findings of the study show that subjects used the simple past tense in the context of a past-completed event. The use of the simple past tense in the context of a past-completed event might be attributed to transfer from the l1 or might be considered as a consequence of positive learning. The results further show that subjects have transferred more explicit knowledge than implicit. And the results have ruled out the l2-status factor claim that the l2 is the privileged source of transfer in l3 acquisition.
Keywords: third language acquisition; Lingala-French; English